Новые данные по морфологии средиземноморского геккона, Mediodactylus kotschyi danilewskii (Reptilia, Gekkonidae), в Крыму - (:unkn) unknown (My University, 2005)
Впервые изучена морфологическая изменчивость средиземноморского геккона, Mediodactylus kotschyi danilewskii (Strauch, 1887), на всем протяжении его ареала в Крыму, в том числе в популяциях, населяющих естественные ландшафты. Констатирован высокий уровень межпопуляционной изменчивости. Наибольшим своеобразием на фоне всех крымских популяций выделяются экзоантропные популяции крайней юго-западной части южного берега Крыма (участок пгт Балаклава — мыс Айя — мыс Сарыч). Сходство синантропных группировок Гераклейского п-ова (г. Севастополь) и западных окр. Алушты (участок пгт Артек — мыс Аюдаг — пгт Карасан) позволяет предполагать их генетическое родство. Анализ изменчивости интродуцированной в 1980 г. из Херсонеса группировки горы Святая (Карадагский заповедник, юго-восточное побережье Крыма) свидетельствует о значительной роли «принципа основателя» в становлении фенооблика популяций. Морфологическая изменчивость M. kotschyi из всех крымских популяций по большинству признаков укладывается в диапазон изменчивости подвида M. k. danilewskii.
New Data on Morphology of the Mediterranean (Kotschyi's) Gecko, Mediodactylus kotschyi danilewskii (Reptilia, Gekkonidae) in Crimea
For the first time, the morphological variability of the Mediterranean gecko Mediodactylus kotschyi danilewskii (Strauch, 1887) was studied in all parts of its range in the Crimean Peninsula, including the populations inhabiting natural landscapes. High level of intracpecific variability is revealed. Exoanthropic populations of the westernmost part of the Southern Crimean Coast between Balaklava and Cape Sarych are characterized by maximal peculiarity among all others. The similarity between synanthropic populations of the Geraklean Peninsula (Sevastopol) and the central sector of the Southern Coast (settlement Artek — Cape Aju-Dagh — settlement Karasan) probably results from their genetic relationship. Analysis of the variability in the population of Svyataya Mountain (the Karadagh Reserve, South-Eastern Crimean Coast), which was introduced from Khersones (Sevastopol) in 1980, shows that "the principle of founder" plays important role in the formation of morphological appearance of populations. Morphological variability of M. kotschyi in all Crimean populations lays within the range of variability of the subspecies M. k. danilewskii.
Keywords: Mediodactylus kotschyi danilewskii; Крым; морфологическая изменчивость